2021
DOI: 10.3390/vaccines9111250
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Hesitancy in a City with Free Choice and Sufficient Doses

Abstract: Background: Vaccine hesitancy represents one of the major global health issues around the world. We examined the perception, attitude, perceived barriers and facilitation measures of receiving the COVID-19 vaccine in a Chinese population with free vaccine choices (Sinovac [Coronavac] vs. BioNTech/Fosun [Comirnaty]) and adequate doses. Method: We conducted a random telephone survey of the general population in 1195 subjects aged 18 years or above from 23 April 2021 to 8 May 2021 after two months of vaccine roll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 17 publications
6
47
0
Order By: Relevance
“…This study observed a fairly low prevalence of COVID-19 vaccination intention in the next six months among unvaccinated and unscheduled adults aged 18-70 in Hong Kong (14.5% and 22.8% at about three and six months since the vaccine rollout, respectively). The latter was comparable to the 25.1% reported in another local study among unvaccinated adults who had been surveyed two months after the beginning of the rollout [17]. People with a low vaccination intention might be hesitating, waiting to see [15], or refusing COVID-19 vaccination firmly [6].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This study observed a fairly low prevalence of COVID-19 vaccination intention in the next six months among unvaccinated and unscheduled adults aged 18-70 in Hong Kong (14.5% and 22.8% at about three and six months since the vaccine rollout, respectively). The latter was comparable to the 25.1% reported in another local study among unvaccinated adults who had been surveyed two months after the beginning of the rollout [17]. People with a low vaccination intention might be hesitating, waiting to see [15], or refusing COVID-19 vaccination firmly [6].…”
Section: Discussionsupporting
confidence: 79%
“…This study is the first one reporting a significant association between the perceived travel-related advantage and COVID-19 vaccination intention, which was stronger in this study than the widely reported association between the perceived benefits of protection and vaccination intention [31,35]. Consistently, another local study found that "vaccine passports for overseas travel" was the strongest among a list of incentives for COVID-19 vaccination (e.g., relaxation of social distancing and granting work leave to vaccinated people) [17]. The pandemic has made international travel difficult.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The prevalence of behavioral intention of COVID-19 vaccination remained low in Hong Kong during the initial post-rollout period (25.1%) [41] while similar data was unavailable in other countries for comparisons. The actual vaccination rate during the initial rollout period in Hong Kong (say May 2021) was lower than those of some seriously affected countries (e.g., U.S. and U.K.) but was comparable to or even higher than others (e.g., Australia, Singapore, Japan, and Thailand) [3] .…”
Section: Discussionmentioning
confidence: 91%
“…Hong Kong government also offered some incentives to motivate people to get vaccinated, such as lottery for winning prizes, exemption of regular COVID-19 testing, allowing visits to elderly homes and hospitals, entering bars/clubs, reducing quarantine duration, and walk-in vaccination services without prior booking [ 3 ]. One study showed that vaccine passports for cross-border travel was most valued by people aged 18 years or above in Hong Kong, followed by allowance to enter entertainment venues [ 29 ]. However, these incentives were not designed specifically for older adults in Hong Kong.…”
Section: Introductionmentioning
confidence: 99%